2017
DOI: 10.3892/ol.2017.6002
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the evaluation of DNA damage and repair mechanisms in cancer

Abstract: DNA lesions and the repair mechanisms that maintain the integrity of genomic DNA are important in preventing carcinogenesis and its progression. Notably, mutations in DNA repair mechanisms are associated with cancer predisposition syndromes. Additionally, these mechanisms maintain the genomic integrity of cancer cells. The majority of therapies established to treat cancer are genotoxic agents that induce DNA damage, promoting cancer cells to undergo apoptotic death. Effective methods currently exist to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 84 publications
0
36
0
Order By: Relevance
“…Surprisingly, DNA damage tended to be distributed in the peripheral pulmonary zone while the airway epithelium displayed inappreciable damage effects. Given that the TUNEL assay is limited in its sensitivity and specificity in detecting DNA damage following apoptosis [ 30 ], we used other assays in the following steps to further confirm the effects.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, DNA damage tended to be distributed in the peripheral pulmonary zone while the airway epithelium displayed inappreciable damage effects. Given that the TUNEL assay is limited in its sensitivity and specificity in detecting DNA damage following apoptosis [ 30 ], we used other assays in the following steps to further confirm the effects.…”
Section: Resultsmentioning
confidence: 99%
“…One major limitation of this study is that we did not directly examine DNA repair. Although analyzing the expressions of DNA repair enzymes as well as performing the OxyBlot study showed how BER was altered within the cells upon cigarette-smoke exposure and lycopene treatment, we admit that extra assays (i.e., comet assay and direct ROS quencher assay [54]) are warranted to further validate the antioxidative efficacy of lycopene in the cells exposed to smoke. These assays will be included in our future direction.…”
Section: Discussionmentioning
confidence: 97%
“…Previous detection methodologies implemented to sense DNA lesions are based on bulk measurements that only provide information on the damage frequency, but not their specific site location along the DNA strands 33,34 . Furthermore, the idea of using high-fidelity sequencing technologies has recently been considered as an additional way to detect DNA-nicks.…”
Section: Introductionmentioning
confidence: 99%